ChemInform Abstract: A Highly Enantioselective Biginelli Reaction Using Self‐Assembled Methanoproline—Thiourea Organocatalysts: Asymmetric Synthesis of 6‐Isopropyl‐3, 4‐dihydropyrimidines. Issue 17 (April 2016) - Hang, Zhijun; Zhu, Jun; Lian, Xiang; Xu, Peng; Yu, Han; Han, Sheng
Abstract: The three‐component reaction of thiourea, aldehydes, and ketoester (III) allows the synthesis of a wide range of pyrimidine derivatives in high yields with excellent enantioselectivities.